The Executioner. 432. Slayground - Pendleton, Don, 1927-1995 (Pendleton, Don, 1927-1995. Executioner, 2014)
"National security is on the line when a senator's daughter disappears from her Florida college. The leader of the cult responsible is desperate to boost his sect's influence by gaining access to the sensitive government information the girl possesses...even if she dies in the process. Needing to act fast, but quietly, the White House sends Mack Bolan deep into the swamplands. Bolan's mission is to rescue the girl before she gives up any secrets, but infiltrating the leader's stronghold is no easy feat. Using the humid, marshy landscape to their advantage, the cult has laced the swamps with armed guards and deadly traps. And when Bolan discovers the sect's most dangerous weapons threaten the mind, not the body, he realizes he'll need more than guns and brawn to win this battle. But the Executioner has put his faith in justice, and he won't quit until his enemies are converted" --